Innovations of Simile-Based Images in Vassâf History - Z Ekhtiyari; M Mahmoodi (متن شناسی ادب فارسی, 2011)
Simile is one of the most prominent elements of dream making in Vassâf history. In this work, Vassâf tries to use figurative elements, especially simile, to make a poetic prose. He uses simile as a tool for making language prominent and adorned. Because there is no corrected version of VassÃ¢fâs history and its complicated prose this valuable book has been often neglected. In this study the simile innovations in VassÃ¢fâs history will come under a closer look. From the structural point of view this article is based on introduction and analysis of different kinds of Persian similes in VassÃ¢fâs history in terms of pillar, sides or parties and form. For analyzing the data, the methods of Persian traditional rhetorics have been used. At the end, on the basis of statistical samples, the status of different types of simile in VassÃ¢fâs history has been shown and they have been compared with other figurative devices. The results of this study show that simile is one of the important elements for making the language of VassÃ¢fâs history prominent and adorned and contributes a lot to make the prose of this work a poetic prose.